2016
DOI: 10.1093/tropej/fmw052
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Daily Activity of Lying Down, Sitting, Standing and Stepping of Obese Children Using the ActivPALTMActivity Monitor

Abstract: This study describes the patterns of objectively measured sitting, standing and stepping in obese children using the activPALTM and highlights possible differences in sedentary levels and patterns during weekdays and weekends. Sixty-five obese children, aged 9-11 years, were recruited from primary schools in Terengganu, Malaysia. Sitting, standing and stepping were objectively measured using an activPALTM accelerometer over a period of 4-7 days. Obese children spent an average of 69.6% of their day sitting/lyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…This study found that children sat in excess of 10hrs/day (68% of wear time) on Children spent more time sitting on weekend days compared to school days in this study. These findings add to previous inconsistent evidence that either supports this finding (21)(22)(23), have found no difference (17,32), or have observed the opposite (6).…”
Section: What This Study Addssupporting
confidence: 79%
See 2 more Smart Citations
“…This study found that children sat in excess of 10hrs/day (68% of wear time) on Children spent more time sitting on weekend days compared to school days in this study. These findings add to previous inconsistent evidence that either supports this finding (21)(22)(23), have found no difference (17,32), or have observed the opposite (6).…”
Section: What This Study Addssupporting
confidence: 79%
“…school days and 11hrs/day (74% of wear time) on weekend days which are high volumes of sitting for this age group. These proportions are almost identical to activPAL data reported in obese Malaysian children (aged 9-11yrs) on school days (68%) and weekend days (73%)(23). Compared to accelerometer data, our results are similar to the proportions of sedentary time observed in British Pakistani and White British girls (65-70%) (aged 10yrs) (6) and higher than that reported in a sample of White British children (64%)(5).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…17 Obese children also were found to accrue the greatest number of sedentary bouts during weekdays rather than at the weekend. 18 Similarly, Lee and colleagues found low levels of physical activity and high levels of sedentary behaviour among children aged 7 to 12 years, with 84.8% not meeting pedometer step count recommendations. 19 The same study also reported that Physical Activity Questionnaire (PAQ) scores and pedometer step counts were negatively associated with body mass index (BMI)-for-age Z-score, percentage body fat and waist circumference (WC).…”
Section: Introductionmentioning
confidence: 94%
“…Full details of participant's recruitment and study procedure have been reported elsewhere [12]. In brief, the present study is a cross-sectional study measuring the daily activity of lying down, sitting, standing and stepping of obese of obese children …”
Section: Methodology Participantsmentioning
confidence: 99%